1989
DOI: 10.1080/00039896.1989.9935882
|View full text |Cite
|
Sign up to set email alerts
|

Dioxins in Cigarette Smoke

Abstract: Dioxins in cigarettes, smoke, and ash were determined using gas chromatography/mass spectrometry. The total concentration of polychlorinated dibenzo-p-dioxins (PCDDs) in cigarette smoke was approximately 5.0 micrograms/m3 at the maximum level, whereas various congeners from tetra-octa-chlorodibenzo-p-dioxin (-CDD) were detected. Particullary, the total concentration of hepta-CDD congeners was the highest among these congeners. Mass fragmentograms of various PCDD congeners were similar to those in flue gas samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 17 publications
0
37
1
Order By: Relevance
“…It is below the TDI proposed by WHO (1-4 pg/kg/d). Consistently, Muto and Takizawa also reported that the daily intake of PCDD by smoking 20 cigarettes was f4 pg/kg body weight/d (6). In contrast to these previous reports, we showed in this report that cigarette smoke has extremely high levels of dioxin-like potential for triggering the AhR-XRE pathway.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…It is below the TDI proposed by WHO (1-4 pg/kg/d). Consistently, Muto and Takizawa also reported that the daily intake of PCDD by smoking 20 cigarettes was f4 pg/kg body weight/d (6). In contrast to these previous reports, we showed in this report that cigarette smoke has extremely high levels of dioxin-like potential for triggering the AhR-XRE pathway.…”
Section: Discussioncontrasting
confidence: 55%
“…Those include PCDD, PCDF, Co-PCB, and benzo(a)pyrene (6,20). However, previous assessment using gas chromatography-mass spectrometric analyses showed that the levels of individual chemicals in cigarette smoke were very low and within permissible ranges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polychlorinated aromatic hydrocarbons (PCAHs) such as polychlorinated biphenyls (PCBs), polychlorinated dibenzo-p-dioxins (PCDDs), and polychlorinated dibenzofurans (PCDFs) are contaminants of the food chain (2), are present in tobacco smoke (3,4) and air (5,6), and accumulate in fat tissue (1,2). Lower chlorinated PCB congeners (e.g., PCB 28,52, and 101) are less cumulative (shorter half-life in the body) than are higher chlorinated congeners (e.g., PCB 138, 153, and 180).…”
mentioning
confidence: 99%
“…In the case of tobacco, a comparison may be warranted also because tobacco smoke causes additional exposure to PCDD/Fs, even at the level of 4 pg TEq kg -1 bw d -1 from 20 cigarettes a day (Muto and Takizawa 1989), a value close to TDI, and causes elevated serum levels especially in women (Fierens et al 2005). Smoking on the other hand influences the pharmacokinetics and body burdens of DLCs (e.g.…”
Section: Comparisons With Other Toxic Agentsmentioning
confidence: 99%